The margins of discretion in transnational administrative acts : expulsion decisions and entry bans following a criminal conviction - Hamenstadt, Kathrin (London [England] : Hart Publishing, 2021)
"'The Margins of Discretion in Transnational Administrative Acts : Expulsion Decisions and Entry Bans Following a Criminal Conviction' analyses the legal rules governing the expulsion of delinquent foreigners through a comparative lens. The monograph begins with a vertical perspective, focusing on the effects of European standards on the law of expulsion and entry bans in Germany, the Netherlands and the United Kingdom. It explores how these countries use their margin of discretion, granted by European law, to solve the societal, political and legal challenges that are posed by delinquent foreigners. Moreover, it highlights the similarities, convergences and differences between these countries' approaches to the topic at hand. Subsequently, the monograph adopts a horizontal perspective by focusing on the effects of national decisions on other states and, thereby, addresses transnational administrative acts. National expulsion decisions and entry bans can be given effect throughout European countries, with the consequence that other states are obliged to enforce them by refusing foreigners access to their territory. This obligation arises despite the fact that expulsion decisions and entry bans are adopted on the basis of diverging national provisions. The resulting tensions call for solutions and recommendations, which are put forward in this book."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Emigration and immigration law -- Europe; Deportation -- Europe; Europe -- Emigration and immigration -- 21st century; Electronic books